Strength training is ineffective for oxidative metabolism - Schantz, P. G.; Kallman, M. (Swimming Technique, 1989)
This study attempted to determine the relationship between strength training program effects and aerobic endurance adaptations. Strength training programs are generally considered to be anaerobic in nature. Muscle biopsies were taken from three groups: 1) strength-trained athletes, 2) endurance-trained swimmers, and 3) a non-trained control group. The strength-trained group exhibited 34% larger mean muscle fiber area and 19% more capillaries per fiber than did the control group. Endurance trained swimmers had an even higher fiber composition and capillary to fiber ratio than the other two groups. Strength training was not shown to affect the enzymes of oxidative metabolism which were increased in the swimmers. One should not expect to gain any endurance benefits from strength training when compared to endurance-trained athletes. However, the increase in capillarization in strength-trained muscles must have a small affect on endurance capacity purely by facilitating oxygen delivery to working muscles as a result of increased capillarization. Implication: It was concluded that strength training does not effect the enzymes associated with aerobic metabolism (some studies say that it does). Consequently, training needs to be specific for the energy system required in the sport. To exceed one's regular training program through extra work, such as dry-land training, may not be harmful, but to decrease training from beneficial sport-specific work by adding auxiliary activities will not help and could even hinder performance development.